In Silico Adme and Toxicity Studies of Derivative Phthalimide Compounds as Non-Nucleoside HIV-1 Reverse Transcriptase Inhibitor - Tiara Ajeng Listyani; Fazlin Fauzi; Ariyanti Ariyanti; Tatiana Siska Wardani (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Phthalimide derivate compounds was reported as a new class of nonnucleoside reverse tranckriptase inhibitors. The aim of this research is to determine the prediction of absorption, distribution, metabolism, and excretion (ADME) as well as the toxicity test of phthalimide-derived compounds which have the best potential as HIV-1 reverse transcriptase enzyme inhibitors. This study used an in silico approach to predict oral bioavailability and toxicity. The prediction of the ADME in this study using SwissADME which is run online where thirty-three phthalimide derivate compounds have molecular weight, hydrogen donor and acceptor bond, and log P ​​that meet the criteria of Lipinski Rules. Prediction of toxicity ​​in this study using in silico method with Toxtree v1.60 and it is known that phthalimide derivate compounds are not carcinogenic and mutagenic.